Erythroxylum sobraleanum (Erythroxylaceae): A new species from Southeastern Brazil - Loiola, Maria Iracema Bezerra; Cordeiro, Luciana Silva (Phytotaxa, 2014)
Erythroxylum sobraleanum (Erythroxylaceae) is described and illustrated as a new species from Minas Gerais, Southeastern Brazil, and positioned in Erythroxylum sect. Archerythroxylum. This species grows in the Seasonal semi-deciduous montane forest, on the Serra da Mantiqueira. It is recognized by the long-triangular stipules, non-striate, membranaceous, 3-setulose, with fimbriolate to entire margin, leaves membranaceous, flowers at the apex of short shoots, and styles connate 2/3 its length in dolichostylous flowers. Affinity relationships with other species of Erythroxylum are presented and discussed.